Answers

2015-05-02T20:02:43+05:30
Let f(x)=(k-2)x²-2x-(k+5).
Since 4 is a zero of f(x), BY FACTOR THEOREM,
f(4)=0
Therefore,
⇒(k-2)(4)²-(2*4)-(k+5)=0
⇒16k-32-8-k-5=0
⇒15k--45=0
⇒15k=45
⇒k=45/15
Therefore, k=3.






HOPING THAT IT WILL HELP YOU!!!
1 5 1
2015-05-03T02:23:24+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
4  is a root / zero  of    polynomial
         P(x)  =   (k-2) x²  - 2 x  - (k+5)

    =>  P(4) = 0
    =>  (k - 2) 4²  - 2 * 4 - (k+5)  = 0
    =>  15 k - 45 = 0   

              =>  k = 3

1 5 1
please click on thanks azur blue button above